Valorization of pomegranate peels: a biorefinery approach - Pathak, P. D.; Mandavgane, S. A.; Kulkarni, B. D. (Waste and Biomass Valorization, 2017)
Recent studies have shown that pomegranate peels (PP) is a valuable source of valuable bioactive compounds, most of which can be converted into value-added products. We herein review this conversion process and provide an outline on the chemical composition of PP and the possible value-added products that can be produced from this commonly discarded agro-waste. We have also discussed its use as a substrate to produce medicinal compounds and bioactive phenolic compounds (e.g., phenolic acids, flavonoids, vitamin C, fertilizers, dietary fibers, and tannins) as well as its use in nanomaterial synthesis. Based on available evidence, it is obvious that PP has a wide variety of applications, and thus, developing an efficient system to utilize PP adequately will help to completely utilize its potential benefits. The biorefinery approach shows promising potential for efficient utilization of PP; however, additional studies should be conducted in this area. © 2016, Springer Science+Business Media Dordrecht.

Valorization of potato peel: a biorefinery approach - Pathak, P. D.; Mandavgane, S. A.; Puranik, N. M.; Jambhulkar, S. J; Kulkarni, B. D. (Critical Reviews in Biotechnology, 2017)
Potato is the fourth main crop consumed worldwide and is an important constituent in the human diet. Consequently, potato is widely used in food-processing industries. However, these industries generate massive amounts of potato peel (PP) as a by-product, which is usually considered a waste, and is discarded. Interestingly, recent research suggests that PP is a valuable source of bioactive compounds, which can be converted into value-added products. In this study, we review the physicochemical composition and valorization of PP. In addition to being used as a dietary fiber or medicine, the value-added products obtained by the fermentation of PP have multiple uses, including their use as adsorbents, biocomposites and packaging materials. These products can also be used in energy production, biopolymer film development, corrosion inhibition and the synthesis of cellulose nanocrystals. The biorefinery approach for PP will increase the value of this waste by producing an array of value-added products and reducing extensive waste generation.
Keywords: Bioactive compounds; Biorefinery; Potato peel; Valorization; Value-added products

Valorization of cow urine and dung: A model biorefinery (2018) - Mandavgane, S. A.; Kulkarni, B. D. (Waste and Biomass Valorization, 2020)
Cow is one of the most common livestock of Indian farmers. Small farm households are strongly dependent on livestock for income as it contributes nearly 16% of their total earnings. As much as two-thirds of rural community depends on livestock for their livelihood. Farmers in India maintain a hybrid farming system, that is, a combination of crop cultivation and livestock, which are complementary to each other. Traditionally, the output of one enterprise is the input of another enterprise. Recent research suggests that in addition to milk, urine and dung obtained from cow are valuable resources of bioactive compounds, which can be converted into value-added products. In this review, we provide an outline for the physicochemical composition and valorization of cow urine and dung. They are utilized in agriculture as a pesticide, manure, and acts as a soil rejuvenator. Cow dung is used for bio energy production by fermentation and gasification. Medicinal and cosmetic products are prepared following ayurvedic formulations described in ‘Panchagavya’. Cow dung ash is used as adsorbent, construction material, mosquito repellent and electrolyte. A case study of manufacturing unit producing arrays of products from cow urine and dung is also presented.
Keywords: Bio gas; Cow dung; Cow urine; Waste utilization